2007
DOI: 10.1158/1535-7163.mct-06-0614
|View full text |Cite
|
Sign up to set email alerts
|

P276-00, a novel cyclin-dependent inhibitor induces G1-G2 arrest, shows antitumor activity on cisplatin-resistant cells and significant in vivo efficacy in tumor models

Abstract: P276-00, a flavone that inhibits cyclin-dependent kinases, has been identified by us recently as a novel antineoplastic agent. In this study, we have selected a panel of human tumor cell lines and xenografts to allow determination of selectivity and efficacy of P276-00. When tested against a panel of 16 cisplatin-sensitive and cisplatin-resistant cell lines, the antiproliferative potential of P276-00 was found to be f30-fold higher than cisplatin. Studies to show tumor sensitivity using clonogenic assay in 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 24 publications
(7 reference statements)
2
50
0
Order By: Relevance
“…18,19 The drug was dissolved in dimethyl sulfoxide (DMSO; Sigma Chemical, St Louis, MO, USA) at a concentration of 200 mmol/l (200 mM) and stored at À20 1C until use; it was diluted in culture medium (1-4000 nM, o0.1% DMSO in the final concentration) immediately before use and was used within 4 h.…”
Section: P276-00mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The drug was dissolved in dimethyl sulfoxide (DMSO; Sigma Chemical, St Louis, MO, USA) at a concentration of 200 mmol/l (200 mM) and stored at À20 1C until use; it was diluted in culture medium (1-4000 nM, o0.1% DMSO in the final concentration) immediately before use and was used within 4 h.…”
Section: P276-00mentioning
confidence: 99%
“…Given the crucial role played by the cyclins in MM, and specifically cyclin D1, in 50% of MM, we asked in the present study: (1) whether targeting cyclin D1 in MM was of potential therapeutic benefit; (2) whether P276-00, 18,19 a known smallmolecule cyclin-dependent kinase (Cdk) inhibitor with activity against Cdk4/cyclin D1 had preclinical activity in MM and (3) whether combining P276 with other novel and conventional agents would provide improved efficacy in MM.…”
Section: Introductionmentioning
confidence: 99%
“…11 In vitro and in vivo xenograft studies have demonstrated that P276-00 is effective against a broad spectrum of human cancer cell lines. 12 We found that P276-00 inhibits HIF-1-dependent induction of luciferase in U251-HRE cells by inhibiting hypoxic accumulation of HIF-1a. In this study, prostate cancer cells (PC-3 and DU145) were used to explore the mechanism through which P276-00 inhibits activity of HIF-1.…”
Section: Introductionmentioning
confidence: 67%
“…12 However, in spite of being a HIF-1 inhibitor, P276-00 inhibits HIF-1a SM Manohar et al it did not show enhanced cytotoxic activity on prostate cancer cells under hypoxia. Hence, to further study its effects on cell cycle under hypoxia, flow cytometric analysis of PC-3 and DU145 cells cultured for 24 h under hypoxia in a medium containing various concentrations of P276-00 was carried out.…”
Section: Discussionmentioning
confidence: 96%
“…Screening of about hundred compounds structurally related to flavopiridol identified P276-00 as potent Cdk specific inhibitor with moderate selectivity for Cdk1, Cdk4, and Cdk9 (Joshi et al, 2007a). Similar to flavopiridol, P276-00 showed antiproliferative and proapoptotic activity in human breast, colon, lung, prostate carcinoma, and promyelocytic leukemia cell lines in vitro (Joshi et al, 2007b). Decreased Rb phosphorylation, G 1 / G 2 phase arrest, and caspase-dependent apoptosis could be observed in preclinical studies with multiple myeloma cells in vitro and in vivo (Manohar et al, 2011;Raje et al, 2009).…”
Section: Overview Of Small Molecule Cdk Inhibitors: Selectivity and Mmentioning
confidence: 99%